High Prevalence of NRTI and NNRTI Drug Resistance Among ART-Experienced, Hospitalized Inpatients. (1st July 2021) - Bossard, Claire; Schramm, Birgit; Wanjala, Stephen; Jain, Lakshmi; Mucinya, Gisèle; Opollo, Valarie; Wiesner, Lubbe; van Cutsem, Gilles; Poulet, Elisabeth; Szumilin, Elisabeth; Ellman, Tom; Maman, David
Abstract : Background: Patients hospitalized with advanced HIV have a high mortality risk. We assessed viremia and drug resistance among differentiated care services and explored whether expediting the switching of failing treatments may be justified. Setting: Hospitals in the Democratic Republic of (DRC) Congo (HIV hospital) and Kenya (general hospital including HIV care). Methods: Viral load (VL) testing and drug resistance (DR) genotyping were conducted for HIV inpatients ≥15 years, on first-line antiretroviral therapy (ART) for ≥6 months, and CD4 ⩽350 cells/µL. Dual-class DR was defined as low-, intermediate-, or high-level DR to at least 1 nucleoside reverse transcriptase inhibitor and 1 non-nucleoside reverse transcriptase inhibitor. ART regimens were considered ineffective if dual-class DR was detected at viral failure (VL ≥1000 copies/mL). Results: Among 305 inpatients, 36.7% (Kenya) and 71.2% (DRC) had VL ≥1000 copies/mL, of which 72.9% and 73.7% had dual-class DR. Among viral failures on tenofovir disoproxil fumarate (TDF)-based regimens, 56.1% had TDF-DR and 29.8% zidovudine (AZT)-DR; on AZT regimens, 71.4% had AZT-DR and 61.9% TDF-DR, respectively. Treatment interruptions (≥48 hours during past 6 months) were reported by 41.7% (Kenya) and 56.7% (DRC). Approximately 56.2% (Kenya) and 47.4% (DRC) on TDF regimens had tenofovir diphosphate concentrations <1250 fmol/punch (suboptimal adherence). Among viral failures with CD4 <100 cells/µL, 76.0% (Kenya) and 84.6% (DRC) were on ineffective regimens. Conclusions: Many hospitalized, ART-experienced patients with advanced HIV were on an ineffective first-line regimen. Addressing ART failure promptly should be integrated into advanced disease care packages for this group. Switching to effective second-line medications should be considered after a single high VL on non-nucleoside reverse transcriptase inhibitor–based first-line if CD4 ⩽350 cells/µL or, when VL is unavailable, among patients with CD4 ⩽100 cells/µL. Abstract : Supplemental Digital Content is Available in the Text.